A branch-and-price algorithm for the Minimum Latency Problem. (May 2018) - Bulhões, Teobaldo; Sadykov, Ruslan; Uchoa, Eduardo
Highlights: A new branch-and-price algorithm for Minimum Latency Problem is proposed. The new algorithm relies on new features for the ng-path relaxation. Experiments shows that several previously open instances can now be solved. The new features can be potentially applied to other routing problems. Abstract: This paper deals with the Minimum Latency Problem (MLP), a variant of the well-known Traveling Salesman Problem in which the objective is to minimize the sum of waiting times of customers. This problem arises in many applications where customer satisfaction is more important than the total time spent by the server. This paper presents a novel branch-and-price algorithm for MLP that strongly relies on new features for the ng -path relaxation, namely: (1) a new labeling algorithm with an enhanced dominance rule named multiple partial label dominance; (2) a generalized definition of ng -sets in terms of arcs, instead of nodes; and (3) a strategy for decreasing ng -set sizes when those sets are being dynamically chosen. Also, other elements of efficient exact algorithms for vehicle routing problems are incorporated into our method, such as reduced cost fixing, dual stabilization, route enumeration and strong branching. Computational experiments over TSPLIB instances are reported, showing that several instances not solved by the current state-of-the-art method can now be solved.